Enhancing Visual Cryptography Using Digital Watermarking - Elizabeth Rajan, Shobha; Sreedevi, P (International Journal of Computer Sciences and Engineering, 2025)
The Visual Cryptography is an efficient cryptographic scheme which uses the human visual system (HVS) characteristics to decrypt images. But the factor that degrades its efficiency is that it is prone to attacks since OR or XOR operations are used for its decryption (HVS). In order to enhance the security factor of visual cryptographic scheme, watermarking of the encrypted images is proposed. Here we consider the Color Extended VC scheme and Intermediate Significant Bit (ISB) based watermarking technique. The shares produced through VC are watermarked on a host image and is made capable of securely transmitting through even attack prone communication channel.